(untitled) (Damascus University Journal for engineering sciences, 2021)
Ground water tanks have been severely damaged during past earthquakes, and this constituted a great incentive for the researchers for understanding and predicting the seismic behavior of these types of structures. In addition, seismic analysis of reservoirs containing liquid requires special studies different from the analysis of buildings where the fluid inside the tanks applies hydrodynamic forces to tank elements (walls and base). Evolution of liquid hydrodynamic pressures during an earthquake is important for structural design. In this paper, the finite element method FEM and the analytical method were applied through the two methodologies, CEL Coupled lagrange Euler approach which depends on the nonlinear wave theory, and the Coupled Acoustic System wave method methodology which is based on the linear wave theory. The results of the seismic response for finding the hydrodynamic pressure and the Sloshing displacement of the liquid in the cylindrical ground tanks in the state fixed base obtained from this study are found to be in close accordance between the Finite element approaches and analytical method (Eurocode method (. In addition, the study showed the possibility of using the finite element methods in order to find the distribution of the hydrodynamic pressures on the tanks elements by using two approaches Acoustic Method and Coupled lagrange Euler method and the results are very close by percent 95% corresponding with analytical method. In addition, we can use this approaches to find the values of wave height which the difference not exceed 15 %. The impulsive, convective, and total hydrodynamic pressures are investigated for two aspect ratios for cylindrical tanks 0.6 which presents the thin tanks and 1.8 the broad tanks.